Perbedaan Stres Ditinjau dari Ibu bekerja dan Ibu Tidak Bekerja - Pirous Apreviadizy; Ardhiana Puspitacandri (University of Merdeka Malang, 2014)
This study aimed to know the difference of stress between employed mother and unemployed mother. The populations of this study were employed mothers and unemployed mothers in Perumahan PDAM Kelurahan Sidokare. The sample used in this study amounted to eighty respondents. The sampling technique in this study used a sample saturated, where the sampling technique used a full member of the population. Analysis of data in this study used t-test analysis. From the results, t-test = 8.257; sig = 0.000 0.05, which showed difference in stress between employed mothers and unemployed mothers, where a lot of stress experienced at employed mothers (mean 35.88), rather than the unemployed mother (mean 25.85).